A review on analysis and development of solar flat plate collector. (January 2017) - Pandey, Krishna Murari; Chaurasiya, Rajesh
Abstract: Solar flat plate collectors are devices used to trap solar thermal energy and use it for heating applications like water heating, room heating and other industrial applications. Flat plate collectors are popular for low and medium heating applications and there are undergoing constant development in terms of size reduction and enhanced efficiency. This paper presents an overview on the different techniques that are employed to enhance the efficiency of flat late collectors. Effect of using nanofluids as heat transfer fluid, effect of altering absorber plate design for better capture of radiation, methods of heat loss reduction, use of polymer, employing mini channels for fluid flow, using PCM (phase changing materials) to provide heat during night without tank and effect of use of enhancement devices like inserts and reflector have been discussed in this paper. A brief insight on various techniques used to analyse the effects and various designs has also been presented with the development methodology. Some analytical studies and CFD models have also been mentioned. This review paper also deals with the suggestions for the research work which can be carried out in the direction of heat transfer from solar flat plate collectors.